1994
DOI: 10.1055/s-2007-1001901
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Bis-Aldonic Acid Amides and Their Anticoagulant and Antithrombotic Properties

Abstract: Aprosulate sodium was the first representative of a new class of synthetic polyanions showing antithrombotic efficacy in different animal models. In several clinical trails (Phase I) in human volunteers aprosulate demonstrated anticoagulant properties, too. Searching for other active substances of similar structure, a series of bis-aldonic acid amides were synthesized. These compounds exhibited interesting antithrombotic and anticoagulant activities. The pharmacodynamic activities of the compounds LW 10121, LW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…These results encouraged researchers to synthesize some other derivatives with close structural resemblance to aprosulate sodium [62] (Table 6). Both the sugar units and the chain length were varied.…”
Section: Bis-aldonic Acid Amidesmentioning
confidence: 99%
“…These results encouraged researchers to synthesize some other derivatives with close structural resemblance to aprosulate sodium [62] (Table 6). Both the sugar units and the chain length were varied.…”
Section: Bis-aldonic Acid Amidesmentioning
confidence: 99%
“…[2] As far as diorganotin(IV) moieties with acidic carbohydrates derivatives are concerned, it has been shown that the sugar often acts as dianionic chelating ligand, via carboxylate and suitable alkoxidic groups, even at low pH. [4 -6] Aldonic acids are a class of acidic carbohydrates derivatives used in industrial, [7,8] medical [9,10] and cosmetic [11 -13] applications or as intermediates in organic synthesis. [14 -16] An IR and Mössbauer solid-state study of a hydrated dibutyltin(IV) gluconate compound (Bu 2 SnGlun · H 2 O) and a potentiometric and 13 C NMR solution investigation of Me 2 SnGlun have been already reported.…”
Section: Introductionmentioning
confidence: 99%
“…Aprosulate (Luitpold Pharma Munich, Germany) has a molecular weight of 2,388 d. In vitro and ex vivo it prolongs activated partial thromboplastin time (aPTT), thrombin time, and Heptest (Haemachen Int., St. Louis, MO, USA) in different animal and human plasmas (5)(6)(7)(8). In contrast to UFH and LMWH it has very little anti-IIa-and no antiXa-effect.…”
mentioning
confidence: 99%
“…Bislactobionic acid amides as aprosulate, a new class of fully synthesized highly sulfated synthetic glycosaminoglycans were developed with the aim to obtain antithrombotic drugs with a low risk of bleeding in comparison with unfractionated heparin (UFH) or low molecular weight heparins (LMWHs) (1)(2)(3)(4). Aprosulate (Luitpold Pharma Munich, Germany) has a molecular weight of 2,388 d. In vitro and ex vivo it prolongs activated partial thromboplastin time (aPTT), thrombin time, and Heptest (Haemachen Int., St. Louis, MO, USA) in different animal and human plasmas (5)(6)(7)(8). In contrast to UFH and LMWH it has very little anti-IIaand no anti-Xa-effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation